2001
DOI: 10.1042/bj3600513
|View full text |Cite
|
Sign up to set email alerts
|

The Phox homology (PX) domain, a new player in phosphoinositide signalling

Abstract: Phosphoinositides are key regulators of diverse cellular processes. The pleckstrin homology (PH) domain mediates the action of PtdIns(3,4)P # , PtdIns(4,5)P # and PtdIns(3,4,5)P $ , while the FYVE domain relays the pulse of PtdIns3P. The recent establishment that the Phox homology (PX) domain interacts with PtdIns3P and other phosphoinositides suggests another mechanism by which phosphoinositides can regulate\integrate multiple cellular events via a spectrum of PX domain-containing proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(37 citation statements)
references
References 179 publications
(257 reference statements)
1
34
0
1
Order By: Relevance
“…SNX27 lacks a recognized BAR domain, is the only known family member containing a PDZ domain, and, except for its PX domain, is largely distinct from other sorting nexins. It is interesting to note that sorting nexin 17 (SNX17), although it lacks a PDZ domain, shares homology with SNX27 elsewhere (Xu et al, 2001) and has been found to promote recycling of the low-density lipoprotein receptor-related protein (LRP) by interacting with a tyrosine-based sequence distinct from a PDZ motif (van Kerkhof et al, 2005). SNX27 could potentially function via PDZ-dependent inhibition of receptor interaction with the lysosomal sorting machinery or, alternatively, by promoting PDZ-directed packaging of receptors into recycling vesicles.…”
Section: Resultsmentioning
confidence: 99%
“…SNX27 lacks a recognized BAR domain, is the only known family member containing a PDZ domain, and, except for its PX domain, is largely distinct from other sorting nexins. It is interesting to note that sorting nexin 17 (SNX17), although it lacks a PDZ domain, shares homology with SNX27 elsewhere (Xu et al, 2001) and has been found to promote recycling of the low-density lipoprotein receptor-related protein (LRP) by interacting with a tyrosine-based sequence distinct from a PDZ motif (van Kerkhof et al, 2005). SNX27 could potentially function via PDZ-dependent inhibition of receptor interaction with the lysosomal sorting machinery or, alternatively, by promoting PDZ-directed packaging of receptors into recycling vesicles.…”
Section: Resultsmentioning
confidence: 99%
“…Since deletion of these effectors does not lead to all the defects associated with loss of Fab1p, additional effectors remain to be identified. Other proteins that can bind PtdIns(3,5)P 2 (Xu et al, 2001;Cozier et al, 2002) seem unlikely to mediate any of the known effects of this lipid.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these truncated forms would be expected to compete with IRAS-M for membrane anchoring and protein-protein assembly, because the respective PX and leucine-rich repeat domains of IRAS-M are encoded within the first 510 aas. 9,10 Because only transfections with IRAS-M and IRAS-L led to I 1 binding sites in CHO cells (TABLE 3), it seems that the most severely truncated form of IRAS (IRAS-S) lacks the aas necessary to encode an imidazoline binding site. The binding domain for imidazolines has previously been suggested to require acidic aas-specifically those in region #622 through 698 of IRAS-M. 3 IRAS-L also lacks this acidic region but still has imidazoline binding capacity (TABLE 3).…”
Section: Discussionmentioning
confidence: 99%